Andrade-Oliveira Salvianolic Acid B Modulates Caspase-1–Mediated Pyroptosis in Renal Ischemia-Reperfusion Injury via Nrf2 Pathway - Pang, Yu; Zhang, Pei-chun; Lu, Rui-rui; Li, Hong-lian; Li, Ji-cheng; Fu, Hong-xin; Cao, Yi-Wen; Fang, Guo-xing; Liu, Bi-hao; Wu, Jun-biao; Zhou, Jiu-yao; Zhou, Yuan (Frontiers in Pharmacology, 2020)
Acute kidney injury (AKI) is a serious disease characterized by a rapid decline in kidney function. Oxidative stress is the primary pathogenesis of AKI. Salvianolic acid B (SalB), a water-soluble compound extracted from Salvia miltiorrhiza, possesses a potent antioxidant activity. Here, we investigated the protective effect of SalB against renal ischemia-reperfusion injury(I/R) in mice. Briefly, by analyzing renal function, oxidative stress markers and inflammatory biomarkers, we found that SalB could improve kidney damage, reduce oxidative stress and inflammatory factor levels. Interestingly, the expression of the NLR family pyrin domain-containing 3 (NLRP3), caspase-1, pyroptosis related proteins gasdermin D (GSDMD) and interleukin (IL)-1β, which were significantly up-regulated in the kidney tissues of I/R group, was effectively reversed by SalB. Meanwhile, renal tubular epithelial cells hypoxia and reoxygenation model was used to explore pyroptosis of caspase-1-dependent. Further mechanism study showed that the SalB pretreatment could promote the increase of nuclear factor erythroid-2 related factor 2 (Nrf2) nuclear accumulation, which significantly suppressed oxidative stress, pro-inflammatory cytokines, NLRP3 inflammasome activation and pyroptosis. These results indicate that SalB can inhibit caspase-1/GSDMD-mediated pyroptosis by activating Nrf2/NLRP3 signaling pathway, resulting in alleviating I/R injury in mice.